Spiral structure of the third galactic quadrant and the solution to the Canis Major debate - Moitinho, A. (2006)
With the discoveryofthe Sagittarius dwarf spheroidal, agalaxy caughtinthe processofmerging with the Milky Way, the hunt for other such accretion events has become a very active field of astrophysical research. The identification of a stellar ring-like structure in Monoceros, spanning more than 100°, and the detection of an overdensity of stars in the direction of the constellation of Canis Major (CMa), apparently associated to the ring, has led to the widespread belief that a second galaxy being cannibalized by the Milky Way had been found. In this scenario, the overdensity would be the remaining core of the disrupted galaxy and the ring would be the tidal debris left behind. However, unlike the Sagittarius dwarf, which is well below the Galactic plane and whose orbit, and thus tidal tail, is nearly perpendicular to the plane of the Milky Way, the putative CMa galaxy and ring are nearly co-planar with the Galactic disc. This severely complicates the interpretation of observations. In this Letter, we show that our new description of the Milky Way leads to a completely different picture. We argue that the Norma-Cygnus spiral arm defines a distant stellar ring crossing Monoceros and the overdensity is simply a projection effect of looking along the nearby local arm. Our perspective sheds new light on a very poorly known region, the third Galactic quadrant, where CMa is located.